Emission of inorganic PM10 from included mineral matter during the combustion of pulverized coals of various ranks - Wen, C.; Gao, Xiangpeng; Yu, Yun; Wu, J.; Xu, M.; Wu, Hongwei (Elsevier Ltd, 2015)
Three density-separated (1.41.6 g/cm3) and size-fractioned (6390 µm) Chinese coals (HLH lignite, PDS bituminous coal and CZ anthracite), containing dominantly included mineral matter, were prepared and then combusted in a drop-tube furnace in air at 1400°C. Under the experimental conditions, the yields of particulate matter (PM) with aerodynamic diameters of <1 µm (PM1), 1-10 µm (PM1–10) and <10 µm (PM10) as well as some key PM10-forming elements (e.g., Si, Fe and Mg) follow a rank sequence of the HLH lignite > the PDS bituminous coal > the CZ anthracite. Such a rank dependence is attributed to the discrepancies in the properties of included mineral matter in these coals and the coal combustion characteristics. The partition of Fe in the PM1 from the HLH lignite appears to result from the fragmentation and disintegration of included siderite during coal combustion.